IgG4 related disease presenting in breast tissue. Issue 8 (August 2015) - Brierley, Daniel; Kohlhardt, Stan R.; Fernando, Malee
Abstract This case report illustrates a case of immunoglobulin G4-related disease in the breast, of which there are only a few reports in the English literature. A 49-year-old female presented with an asymptomatic breast lump at routine screening and a needle core was done to exclude a possible lymphoma. Histologically, the appearances fulfilled the diagnostic criteria for immunoglobulin G4-related disease. The patient has been treated conservatively with no surgery or drug regime advocated. The patient is currently assymptomatic six months following diagnosis and under clinical review.